Pemeriksaan Kesehatan dan Edukasi Penggunaan Obat untuk Meningkatkan Kesadaran Kesehatan Masyarakat di Padang Panjang - Dita Permatasari; Dini Hanifa; Dian Ayu Juwita; Syofyan; Sundari Anisa Angelica; Rasika Indri Pratiwi; Wiwing Nadia Putri (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
Low public awareness of routine health monitoring and knowledge of proper medication use remains a significant problem, leading to increased adverse drug reactions and a decline in health status. Furthermore, a lack of health literacy and high self-medication practices also increase the risk of inappropriate medication use. To address this need, this activity combines health screening and medication education as an integrative approach to improving public health awareness and drug literacy. This study used a quasi-experimental one-group pre-posttest design and was conducted on 24 October 2025, at SDN 07 Ganting, East Padang Panjang, involving 34 participants. Activities included blood pressure, glucose, cholesterol, and uric acid screenings; medical consultations; and medication education and counseling. The majority of participants were women (80%), with a dominant age range of 41–59 years (50%). Mean blood pressure was 129.1 ± 25.0/86.26 ± 13.60 mmHg, glucose 132.41 ± 74.5 mg/dL, cholesterol 214.7 ± 33.8 mg/dL, and uric acid 5.6 ± 1.8 mg/dL, indicating the presence of risk factors requiring monitoring. Knowledge levels were in the good category at both pre-test (90%) and post-test (93.3%), with no significant difference (p = 0.541). This activity contributed to strengthening drug literacy through direct education linked to screening findings, enabling participants to understand their personal health risks. This integrated screening-education approach shows potential as a more effective community intervention model in increasing public knowledge and awareness of health and the safe use of drugs.